Maternal Near Miss in Patients with Systemic Lupus Erythematosus - Silva, Arlley Cleverson Belo da; Sun, Sue Yazaki; Campanharo, Felipe Favorette; Morooka, Letícia Tiemi; Cecatti, José Guilherme; Mattar, Rosiane (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2023)
Objective Systemic lupus erythematosus (SLE) may cause irreversible organ damage. Pregnancy with SLE may have severe life-threatening risks. The present study aimed to determine the prevalence of severe maternal morbidity (SMM) in patients with SLE and analyze the parameters that contributed to cases of greater severity.Methods This is a cross-sectional retrospective study from analysis of data retrieved from medical records of pregnant women with SLE treated at a University Hospital in Brazil. The pregnant women were divided in a control group without complications, a group with potentially life-threatening conditions (PLTC), and a group with maternal near miss (MNM).Results The maternal near miss rate was 112.9 per 1,000 live births. The majority of PLTC (83.9%) and MNM (92.9%) cases had preterm deliveries with statistically significant increased risk compared with the control group (p = 0.0042; odds ratio [OR]: 12.05; 95% confidence interval [CI]: 1.5–96.6 for the MNM group and p = 0.0001; OR: 4.84; 95%CI: 2.2–10.8 for the PLTC group). Severe maternal morbidity increases the risk of longer hospitalization (p < 0.0001; OR: 18.8; 95%CI: 7.0–50.6 and p < 0.0001; OR: 158.17; 95%CI: 17.6–1424,2 for the PLTC and MNM groups, respectively), newborns with low birthweight (p = 0.0006; OR: 3.67; 95%CI: 1.7–7.9 and p = 0.0009; OR: 17.68; 95%CI: 2–153.6) for the PLTC and MNM groups, respectively] as well as renal diseases (PLTC [8.9%; 33/56; p = 0.0069] and MNM [78.6%; 11/14; p = 0.0026]). Maternal near miss cases presented increased risk for neonatal death (p = 0.0128; OR: 38.4; 95%CI: 3.3–440.3]), and stillbirth and miscarriage (p = 0.0011; OR: 7.68; 95%CI: 2.2–26.3]).Conclusion Systemic lupus erythematosus was significantly associated with severe maternal morbidity, longer hospitalizations, and increased risk of poor obstetric and neonatal outcomes.
Keywords: maternal near miss; severe maternal morbidity; systemic lupus erythematosus; high risk pregnancy; potentially life-threatening conditions